ANALISIS HUKUM TERHADAP SITA JAMINAN YANG DILETAKKAN DI ATAS OBJEK HAK TANGGUNGAN OLEH PENGADILAN - RINTO RINTO (PREMISE LAW JURNAL, 2013)
ABSTRACT The ruling of District Court No.08/CB/2007/306/Pdt.G/2006/PN-Mdn/PN-LP on May 7/2007, related to Disposition of Sequestration No. 08/CB/2007/306/Pdt.G/2006/PN-LP on May 8, 2007 accepted the request on sequestration by Tri Argo Mulyo foundation as the plaintiff of the part of 47.7 hectare of land located at ex-Emplassemen Afdeling Medan Estate, Marindal Estate, PTPN II (persero) in Deli Serdang in order to be the Guarantee for Civil Complaint No. 306/Pdt.G/206/PN-Mdn on September 8, 2006. This case has caused legal problem, for the ruling for sequestration by the District Court cannot be executed in the interest of the plaintiff. This is because the object placed on the sequestration by the District Court has been charged the first degree hypothecation by defendant, PT Pancing Business Center as a debt guarantee to PT Bank Mestika. According to Article 1, paragraph (1) of Hypothecation Law (UUHT) No. 4/1996,” A hypothecation is a security right which is charged on land rights as it is stipulated in Law No.5/1960 on the Principal Provision of Agrarian Law, with or without other objects related to the land to the paying off, the position is prioritized to a certain creditor other than to the other creditors.” Although the ruling about sequestration is placed on the object case (the land) by the District Court, the ruling is void (illusoir) sinct e he position of the creditor as the receiver of hypothecation is prioritized to carry out his rights according to civil law. The condition will, of course, harm the plaintiff and ignore the principle of claiming sequestration (conservatoir beslag) in order to obtain a number of properties from the defendant as collateral for the loss suffered by the plaintiff. Therefore, the judge in the civil case should be careful in using sequestration institution because, if he does not look into the object (the land) as an immovable object and makes a verdict on sequestration haphazardly, the verdict will not have any executorial power. Kata kunci: Sequestration, Object of Hypothecation, Court